Chinese undergraduates' mental health help-seeking behavior: the health belief model - Wang, Haojing; Feng, Zhuowen; Zheng, Zitong; Yang, Jiachen (Frontiers in Psychology, 2024)
The detection rate of mental health problems among undergraduates has recently risen significantly. However, undergraduates underutilize mental health services; approximately a third only of undergraduates in need of treatment use school counseling resources. Based on a social psychological theoretical framework, the health belief model, factors of undergraduates’ willingness to seek help when dealing with psychological problems were investigated. A cross-sectional online questionnaire and a snowball sampling method with 446 undergraduates investigated perceived susceptibility, perceived severity, perceived behavioral benefits, perceived barriers, self-efficacy, and cues to action to understand how students’ mental health-seeking behaviors are affected. We found that perceived susceptibility (p<0.01), perceived severity (p<0.01), perceived benefits (p<0.01), perceived barriers (p<0.01), self-efficacy (p<0.01), and cues to action (p<0.01) significantly correlated with behavioral intention. Encouragement or counseling from others would be more likely to motivate undergraduates to seek mental health help. In addition, we used a bias-corrected Bootstrap approach to test the significance of the mediating effect, the mediation effect of cues to action between undergraduates’ perceived susceptibility and mental health help-seeking behavior was utterly significant (mediation effect value of 0.077, with an SE value of 0.027 and a 95% CI [0.028, 0.133]). It demonstrated that those who perceived themselves to be at high risk of developing a mental illness and who had received encouragement or counselling to seek mental health help were more likely to be motivated to seek mental health help.} Multiple regression analyses indicated that self-efficacy (Z=5.425, p=0.000<0.01) and cues to action (Z=6.673, p=0.000<0.01) independently influenced behavioral intentions. Encouragement or counseling from others would be more likely to motivate undergraduates to seek mental health help.